A suitable enemy : racism, migration and Islamophobia in Europe - Fekete, Liz (Pluto, 2009)
Liz Fekete is a leading authority on issues of racism, Islamophobia and national security legislation. 'A Suitable Enemy' draws on 16 years of research to present a comprehensive overview of EU immigration, asylum, race and security policies.